Presidential Address 39th Annual Conference of the Linguistic Society of Nepal - Regmi, Bhim Narayan (Nepalese Linguistics, 2019)
This Presidential Address was delivered at the Inaugural Ceremony of 39th Annual Conference of the Linguistic Society of Nepal at CEDA Hall, Tribhuvan University, Kirtipur, Kathmandu on 26 November 2018.